Community-Focused Language Documentation in Support of Language Education and Revitalization for St. Lawrence Island Yupik - Schwartz, Lane; Schreiner, Sylvia L.R.; Chen, Emily (Études/Inuit/Studies, 2019)
St. Lawrence Island Yupik, an endangered language of the Bering Strait region spoken by fewer than one thousand people in western Alaska and far eastern Russia, is currently in a state of generational transition. We survey the existing body of Yupik literature and pedagogical resources developed during the twentieth century, examine the context and use of Yupik in the current educational setting, and describe current challenges for teaching the language in the schools. We then outline our integrated approach to language documentation currently being applied to Yupik, and address how existing resources can be integrated into research and development processes in a way that both supports research efforts and results in tangible modern educational tools for the Yupik community on St. Lawrence Island, and eventually in Russia. This approach is intentionally designed to closely integrate research processes from language documentation and computational linguistics such that the results of each research endeavour positively support the other, and such that both disciplines concretely support community-based efforts to revitalize and teach the language. Le yupik de l’île Saint-Laurent, une langue du détroit de Béring en péril, (moins de 1 000 locuteurs habitent dans l’ouest de l’Alaska et l’extrême est de la Russie) est actuellement en période de transition générationnelle. Cet article examine la littérature disponible sur le yupik et les ressources pédagogiques qui se sont développées au cours du XXe siècle. Il étudie également le contexte et l’utilisation du yupik dans le cadre éducatif actuel et décrit les défis liés à l’enseignement de la langue dans les écoles. On décrit ensuite l’approche intégrée de la documentation linguistique appliquée actuellement au yupik et aborde aussi les façons dont les ressources existantes peuvent être intégrées aux processus de recherche et de développement, de manière à soutenir les efforts de recherche et produire des outils pédagogiques modernes et tangibles pour la communauté ...